2022
DOI: 10.15252/embj.2022111158
|View full text |Cite
|
Sign up to set email alerts
|

An apical membrane complex for triggering rhoptry exocytosis and invasion in Toxoplasma

Abstract: Apicomplexan parasites possess secretory organelles called rhoptries that undergo regulated exocytosis upon contact with the host. This process is essential for the parasitic lifestyle of these pathogens and relies on an exocytic machinery sharing structural features and molecular components with free-living ciliates. However, how the parasites coordinate exocytosis with host interaction is unknown. Here, we performed a Tetrahymena-based transcriptomic screen to uncover novel exocytic factors in Ciliata and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 104 publications
(168 reference statements)
1
23
0
Order By: Relevance
“…Only two groups of surface-exposed proteins, MIC8 and the CRMPs, have been specifically associated with rhoptry discharge in T. gondii (Kessler et al , 2008; Singer et al , 2022; Sparvoli et al , 2022). We previously showed that CLAMP depletion does not affect secretion of the microneme protein MIC2 (Sidik et al , 2016b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two groups of surface-exposed proteins, MIC8 and the CRMPs, have been specifically associated with rhoptry discharge in T. gondii (Kessler et al , 2008; Singer et al , 2022; Sparvoli et al , 2022). We previously showed that CLAMP depletion does not affect secretion of the microneme protein MIC2 (Sidik et al , 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…MIC8, a prototypical single-pass transmembrane microneme protein, was the first factor shown to be specifically required for rhoptry discharge in T. gondii (Kessler et al , 2008). More recently, two large multipass transmembrane proteins (CRMPa and CRMPb) were similarly associated with rhoptry discharge and shown to form a complex with two single-pass microneme proteins bearing thrombospondin domains (Singer et al , 2022; Sparvoli et al , 2022). Although the CRMP complex proteins do not localize to micronemes unambiguously (Singer et al , 2022; Barylyuk et al , 2020), they accumulated at the apical end of extracellular parasites (Sparvoli et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations